Hardware trojans and smart manufacturing – a hardware security perspective - Aslam, Sohaib; Samie, Mohammad; Jennions, Ian K. (IOS Press, 2018)
Integrated Circuits (ICs) are the cardinal elements of modern electrical, electronic and electro-mechanical systems. Amid global outsourcing of ICs' design and fabrication and their growing applications in smart manufacturing or Industrie 4.0, various hardware security threats and issues of trust have also emerged. IC piracy, counterfeiting, and hardware Trojans (HTs) are some of the key hardware threats that merit the attention of manufacturing community. It is worth noting that the lower abstraction levels (ICs) are falsely assumed to operate securely. The proposition, therefore, is that if an operating system (higher abstraction level) is considered to be secure while operating on a compromised IC (lower abstraction level), would it be prudent to regard this implementation as secure? The purpose of this paper is to highlight IC level threats with an emphasis on hardware Trojans that pose a significant threat to smart manufacturing environment in the wake of Industrial Internet of Things (IIoT).
Keywords: Industrie 4.0; Integrated Circuits; Hardware Trojans; Smart Manufacturing